Efektivitas Model Pembelajaran Kooperatif Tipe Group Investigation Materi Ekosistem Pada Motivasi Belajar Siswa - Yustina Taek; Vinsensia Ulia Rita Sila; Feliksitas Angel Masing (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
This research aims to determine the effect of the learning model cooperative type group investigation on students' learning motivation on ecosystem material at SMPN Kiupunu. This study is an experimental study and the design in this study is Non-Randomized Post-Test Only Control Group Design. The population in this study was all students of class VII SMPN Kiupunu totaling 36 students and the samples were taken from class VII A and class VII B, each each class is 18. The sampling technique is purposive sampling. The data collection method used is a motivational questionnaire. Based on data from research conducted at SMPN Kiupunu, it shows that there is an effect of applying the group investigation model on the learning motivation of class VII students. This is evidenced by the value of the significance level on the T-test of 0.000. This is where Ho is rejected and Ha is accepted or there is an effect of the application of the group investigation cooperative learning model on the learning motivation of class VII students.